An Exploratory Study on the Practice of Pagsasanto by Openly-Gay Santeros - Piamonte, Samuel Brando H.; Quintos, Mark Anthony M.; Iwayama, Minami O. (Philippine Social Science Journal, 2020)
This exploratory study was conducted to inquire into the experiences of gay santeros – those who take care of religious statues or imahes that are used for Catholic religious activities. The study looked into the entry of the santeros to the practice of pagsasanto, their access to the imahe, their reasons for entering and maintaining the practice, and the benefits that they perceive to derive from it. Through conducting interviews with openly-gay santeros, it was found that early exposure to their religious family, school, and local community influenced them into entering the practice of pagsasanto. On access to the imahe, the participants were either owners of the imahe through purchase, donation or inheritance, or caretakers of the imahe through entrustment by their religious networks. On reasons for entering and maintaining the practice, it was found that such was conducted and maintained for egoistic reasons, self-expression, legacy, or spirituality. Lastly, it was found that advantages on health and subsistence, personal development, and social rewards were the perceived derived benefits from the practice of pagsasanto. These findings suggest implications pertaining to the dynamics of religiosity and non-normative gender identity in the Philippines where the Church finds willing caretakers among gay Catholics while gays find an avenue for the expression of gender identity and creativity in the task given to them.